Maternal body fluid lncRNAs serve as biomarkers to diagnose ventricular septal defect: from amniotic fluid to plasma - Wang, Huaming; Lin, Xi; Wang, Xinda; Liu, Xinxiu; He, Shaozheng; Lyu, Guorong (Frontiers in Genetics, 2023)
Background: Maternal body fluids contain abundant cell-free fetal RNAs, which have the potential to serve as indicators of fetal development and pathophysiological conditions. The study aimed to explore the potential diagnostic value of maternal circulating long non-coding RNAs (lncRNAs) in ventricular septal defect (VSD).The potential of lncRNAs as non-invasive prenatal biomarkers for VSD was evaluated using quantitative polymerase chain reaction (qPCR) and receiver operating characteristic (ROC) curve analysis. The biological processes and regulation network of these lncRNAs were elucidated through bioinformatics analysis.Results: Three lncRNAs (LINC00598, LINC01551, and GATA3-AS1) were found to be consistent in both maternal plasma and amniotic fluid. These lncRNAs exhibited a strong diagnostic performance for VSD, with the AUC of 0.852, 0.957, and 0.864, respectively. The bioinformatics analysis revealed the involvement of these lncRNAs in heart morphogenesis, actin cytoskeleton organization, cell cycle regulation, and protein binding through a competing endogenous RNA (ceRNA) network at the post-transcriptional level. Conclusion: The cell-free lncRNAs present in the amniotic fluid have the potential to be released into the maternal circulation, making them promising candidates for investigating epigenetic regulation in VSD.